THE FIRST EXPERIENCE OF USING SILICONE IMPLANTS IN THE AUGMENTATION GLUTEOPLASTY IN TAJIKISTAN - G.M. KHODZHAMURADOV; M.M. ISMOILOV; M.S. SAIDOV; A.KH. SHAYMONOV (Avicenna Tajik State Medical University, 2017)
The article describes the first experience of the use of silicone gluteal implants with the achievement of the aesthetic effect in 2 young patients aged 24 and 30 years. After a careful individual conversation, the method of placement in each case, there would be a combined procedure: in one observation - directly by gluteal muscle fascia, in the other - a submuscular position. The article notes that regardless of the method of implant placement, in both cases the optimal result was obtained, although there were certain features during the operation and in the postoperative period.